Greece : Fifth Review Under the Stand-By Arrangement, Rephasing and Request for Waivers of Nonobservance of Performance Criteria; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Greece. (IMF Staff Country Reports; Country Report ;, 2011)
The Executive Board approved a three-year Stand-by Arrangement for Greece in the amount of SDR 26.4 billion. Purchases have been made at the time of approval and upon completion of each of the first four reviews. The authorities decided to promote a number of actions, including a further reduction in the public sector salaries, cuts in pensions, the creation of a labor reserve, significant tax expenditure reductions, and the introduction of a property tax. The authorities are accelerating the implementation of structural reforms aimed at promoting employment, investment, and market efficiency.